2011
DOI: 10.1073/pnas.1108564108
|View full text |Cite
|
Sign up to set email alerts
|

Selection of HSV capsids for envelopment involves interaction between capsid surface components pU L 31, pU L 17, and pU L 25

Abstract: During egress from the nucleus, HSV capsids that contain DNA (termed C capsids) are preferentially enveloped at the inner nuclear membrane over capsid types lacking DNA. Using coimmunoprecipitation and biochemical analyses of wild-type and mutant capsids, we identify an interaction between a complex of pU L 17/ pU L 25, termed the C capsid-specific complex (CCSC), and pU L 31, a component of the nuclear egress complex (NEC). We also show that the interactions between these components are dependent on expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
97
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(108 citation statements)
references
References 40 publications
(47 reference statements)
9
97
2
Order By: Relevance
“…Taken together, these results indicated that UL47 formed a complex with UL34, UL31, and/or Us3 in HSV-1-infected cells. This conclusion was in agreement with previous reports (12,21,24) that, in HSV-1-infected cells, UL47 interacted with viral capsid protein UL17, which further formed a complex with UL31 and viral capsid protein UL25, and that UL47 interacted with Us3. At present it remains to be determined whether UL47, UL31, UL34, and Us3 form a high-order complex in HSV-…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Taken together, these results indicated that UL47 formed a complex with UL34, UL31, and/or Us3 in HSV-1-infected cells. This conclusion was in agreement with previous reports (12,21,24) that, in HSV-1-infected cells, UL47 interacted with viral capsid protein UL17, which further formed a complex with UL31 and viral capsid protein UL25, and that UL47 interacted with Us3. At present it remains to be determined whether UL47, UL31, UL34, and Us3 form a high-order complex in HSV-…”
Section: Discussionsupporting
confidence: 83%
“…This hypothesis was supported by the observation in this study that UL47 interacted with UL31 and UL34 in HSV-1-infected cells and that UL47 was a component of primary enveloped virions, which enabled UL47 to interact with the UL34/UL31 complex during primary envelopment. As described above, UL47 was reported to form a complex with UL17, a component of the HSV-1 CVSC, and, therefore, may interact with UL31 to recruit HSV nucleocapsids for primary envelopment (12,13). Therefore, UL47 may upregulate the primary envelopment of nucleocapsids by promoting recruitment of nucleocapsids through interaction with the UL17/UL25/UL31 complex, which may stabilize the association of capsids with the UL34/UL31 complex at the nuclear membrane.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…It is unknown what mechanism selects only DNA-containing capsids for nuclear egress in HCMV-infected cells. In HSV-infected cells, this process is governed by the interaction of the nuclear egress complex and capsid proteins (Yang & Baines, 2011). A similar mechanism may operate in HCMV-infected cells.…”
Section: Exit Of Capsids From the Nucleus: The Nuclear Laminamentioning
confidence: 99%